2012
DOI: 10.1038/sc.2012.70
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI of the cortical sensorimotor system in patients with hereditary spastic paraplegia

Abstract: Our results suggest changes in cortical sensorimotor network function in patients with HSP compared with healthy subjects. Lower activation in patients might reflect damage to the corticospinal tract, be influenced by compensatory mechanisms, and/or be a reflection of neurorehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The indirect evidence of such connection is derived from studies that report two types of findings. First, some found that greater spasticity was correlated with diminished activation in sensory regions [41]. Second, some found that spasticity treatment was associated with changes in sensory network function [16, 19, 42].…”
Section: Discussionmentioning
confidence: 99%
“…The indirect evidence of such connection is derived from studies that report two types of findings. First, some found that greater spasticity was correlated with diminished activation in sensory regions [41]. Second, some found that spasticity treatment was associated with changes in sensory network function [16, 19, 42].…”
Section: Discussionmentioning
confidence: 99%
“…There are 3 studies using fMRI in subjects with HSP (39, 46, 47). In 2 of them, authors employed a motor task to investigate how different cerebral regions are activated in the disease (39, 47). Both studies found abnormal primary motor cortex activation in patients with HSP in comparison to healthy controls; surprisingly, one study found increased whereas the other found reduced activation.…”
Section: Advanced Mri In Hsp: Understanding Pathophysiology and Potenmentioning
confidence: 99%
“…There are no published papers describing neuroimaging findings in patient with KIF5A-ALS. Only one previous work using functional brain MRI described the involvement of the supplementary motor area in SPG-KIF5A patients ( Tomberg et al, 2012 ). The hypometabolism described in ALS10, restricted primarily to the motor region, supports the hypothesis of a predominantly motor involvement related to mutations in this gene, associated with a clinically evident upper motor neuron phenotype.…”
Section: Discussionmentioning
confidence: 99%